Perancangan Augmented Reality sebagai Media Edukasi Gempa Bumi - Yudha Pradana; Riki Oktavian (Jurnal Teknologi dan Rekayasa Manufaktur, 2021)
Education about earthquakes in Indonesia must be optimized. One alternative to optimize education about earthquakes is through augmented reality. The use of augmented reality media is in line with advances in information technology that are also familiar in people's lives. The formulation of the problem in this paper is how to design augmented reality as an earthquake education’s media?. The purpose of writing is to know the design of augmented reality as an earthquake education media. The writing method uses a qualitative approach with data collection techniques through interviews, observation, and literature study. The augmented reality making model uses a waterfall model consisting of analysis, design, implementation, testing, and maintenance. Augmented reality content that contains 3D animation about the types of earthquake processes and earthquakes, as well as 2D animated videos on disaster mitigation that are packaged in a complete and interesting way.